2007
DOI: 10.1634/stemcells.2007-0203
|View full text |Cite
|
Sign up to set email alerts
|

High Histone Acetylation and Decreased Polycomb Repressive Complex 2 Member Levels Regulate Gene Specific Transcriptional Changes During Early Embryonic Stem Cell Differentiation Induced by Retinoic Acid

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 71 publications
7
45
1
Order By: Relevance
“…These results indicate that PINK1 influences H3-K27 trimethylation during neuronal differentiation triggered by RA. Several neuronal differentiation genes, such as Neurogenin 2 (NeuroG2) or Nestin (Nes) (22,44), are targets of PRC2. To evaluate if PINK1 may affect the SH-SY5Y cell differentiation program through regulation of PRC2 function, we quantified by reverse-transcriptionquantitative PCR (RT-qPCR) the expression of the aforementioned PRC2-target genes on PINK1 stably overexpressing or PINK1-silenced SH-SY5Y cells treated with RA.…”
Section: Pink1 Modulates the Differentiation Gene-expression Pattern mentioning
confidence: 99%
“…These results indicate that PINK1 influences H3-K27 trimethylation during neuronal differentiation triggered by RA. Several neuronal differentiation genes, such as Neurogenin 2 (NeuroG2) or Nestin (Nes) (22,44), are targets of PRC2. To evaluate if PINK1 may affect the SH-SY5Y cell differentiation program through regulation of PRC2 function, we quantified by reverse-transcriptionquantitative PCR (RT-qPCR) the expression of the aforementioned PRC2-target genes on PINK1 stably overexpressing or PINK1-silenced SH-SY5Y cells treated with RA.…”
Section: Pink1 Modulates the Differentiation Gene-expression Pattern mentioning
confidence: 99%
“…Global levels of Ezh2 and H3K27me3 decrease when mouse embryonic stem cells differentiate and PRC2 target genes specifically lose Ezh2 binding and H3K27me3 enrichment (28). In addition, two groups found that miR-101 was up-regulated after differentiation of human embryonic stem cell lines (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence of histone acetylation and decompacted chromatin structure, transcription factors and the basal transcriptional machinery are recruited to the region and activate gene transcription (50 -52). Previous study has shown that an increased acetylation of histones H3 and H4 by retinoic acid regulates gene specific transcriptional changes during early embryonic stem cell differentiation (53). ATRA and histone deacetylase inhibitor have been shown to increase Sp1 binding and acetylation of histones H3 and H4 in the promoter of folate receptor (54).…”
Section: Discussionmentioning
confidence: 98%